Acute calcific periarthritis at the metatarsophalangeal joint - a case report - Kyriakos Bekas; Konstantinos Giannikas (Journal of the Foot & Ankle, 2023)
Acute calcific periarthritis (ACP) is an uncommon forefoot condition with a few cases reported in the literature. It is often misdiagnosed and may result in unnecessary diagnostic and therapeutic procedures due to its association with other systemic diseases with similar clinical presentation. A 70-year-old man presented in the emergency room with soft tissue swelling with local erythema and tenderness in the fifth metatarsophalangeal region of the right foot, which started two days prior with no history of injury. Passive and active movements of the joint were painful. Acute calcific periarthritis could be confused with other pathologies. A thorough clinical examination and the knowledge of its clinical presentation could prevent unnecessary diagnostic procedures. Level of Evidence V; Therapeutic Studies; Expert Opinion.